Enrehóyate and Sinámar: participatory socio-praxis in vulnerable spaces in island cities (Gran Canaria, Canarias) - González Ramírez, Federico (2021)
Enrehóyate and Sinámar are two participatory socio-practice experiences in the two most populated cities on the island of Gran Canaria, in the context of the main urban regeneration projects in the Canary Islands: the Las Rehoyas-Arapiles Replacement Plan (Las Palmas de Gran Canaria), a vulnerable space of 2,558 homes, which will be demolished and rebuilt to be inhabited by the same neighbors, and the Integral Plan of the Jinámar Valley (Telde), which aims to the socio-urban transformation in one of the largest public housing neighborhoods in Spain. The main objective of both experiences was the encouragement of latent social networks and the formation of new social capital, through historical analyzers of previous significant neighborhood experiences, which support the construction of new groups of action and neighborhood dialogue, promoted by local institutions, in an early stage of broader citizen participation processes envisaged in both projects. The causes of the weakness of the previous social capital are divergent: accumulation of dependent population and single-parent families, with little social participation, due to the minimum housing of Las Rehoyas; and the traumatic dissolution of the neighborhood social capital caused by the political power, in its founding years, in the Jinámar Valley. The new neighborhood practices emerged from a previous traditional planning of intergenerational training workshops, which allowed the joint reflection of former leaders of neighborhood associations and current representatives of administrative neighborhood communities, and the creation of new platforms and groups.